SLEEP QUALITY (PSQI) AND SUMMATIVE EXAM PERFORMANCE IN MEDICAL STUDENTS - Aleksandra Wądołowska; Blanka Serafin-Juszczak; Maria Wydra; Zuzanna Mogilany; Jan Wojdal; Karolina Kusek; Barbara Przybył; Katarzyna Ciepłucha; Michał Wilk; Daniel Narożniak (International Journal of Innovative Technologies in Social Science, 2025)
Purpose of the research: This study aimed to review the relationship between sleep quality, as measured by the Pittsburgh Sleep Quality Index (PSQI), and academic performance among medical students, highlighting neurocognitive consequences and effective interventions. Materials and methods: The review of research literature was conducted through databases such as PubMed, Google Scholar, and Scopus, including studies from 2007 to 2025. Results: Multiple studies show that poor sleep quality (PSQI >5) is highly prevalent among medical students and often correlates with reduced GPA, impaired memory, and diminished executive function. Acute sleep deprivation before exams significantly worsens performance. However, inconsistent methodologies, self-reported data, and cross-sectional designs limit causal interpretation. Despite this, evidence supports implementing sleep hygiene education, CBT-I, mindfulness training, and institutional changes to promote better sleep and academic outcomes. Conclusions: A multifaceted approach is needed to improve medical students’ sleep. Combining behavioural interventions and structural academic reforms may reduce stress, enhance cognitive performance, and support long-term academic success. Further longitudinal research using objective measures is recommended to strengthen these findings.